EFFECT OF SECOND TOE-TO-HAND TRANSFER ON THE PLANTAR PRESSURE DISTRIBUTION OF THE DONOR FOOT - Li,Bing (2016)
ABSTRACT Objective: To investigate the effect of second toe-to-hand transfer on the plantar pressure distribution of the donor foot. Methods: Twelve normal fresh-frozen cadaveric foot specimens were subjected to an axial load of 600 N. An F-Scan plantar pressure analysis system was used to measure the forefoot plantar pressure. The testing was performed under the conditions of intact second toe, second toe removal with the second metatarsal head reserved, and second toe removal in combination with the distal one-third of the second metatarsal, respectively. Results: The peak pressure of the second metatarsal head was greater than other four forefoot plantar regions. There was no statistically significant change in the forefoot plantar pressure distribution after the second toe was removed (p > 0.05). When the second toe and the distal one-third of the second metatarsal were removed, the forefoot plantar pressure distribution changed significantly (p < 0.05). Conclusions: An intact second metatarsal is essential for the normal distribution of plantar pressure. Removal of the second toe with the second metatarsal head reserved had little influence on the plantar pressure distribution of the donor foot. Removal of the second toe and distal one-third of the second metatarsal resulted in abnormal plantar pressure distribution. Level of Evidence II, Experimental Study.